Methods of preparing aqueous extract and bioactivity of Mentha spicata L. on Raphanus sativus L. seeds - Xavier, Leonardo Pereira; Pires, Andrea; Bonome, Lisandro Tomas da Silva; Moura, Gabriela Silva; Franzener, Gilmar; Fernandes, Aline Pomari (Acta Iguazu, 2020)
The plant interaction knowledge can be applied in several sectors in agriculture such as crop rotation, weed management, green manure and the use of cover crops. Studies on the allelopathic potential of certain plants have been carried out with the application of vegetable extracts on the seeds of a sensitive plant, however, a consensus has not been reached regarding the best way to prepare such extracts. This study aimed to evaluate the efficacy of methods of extraction of allelopathic compounds and the bioactivity of different concentrations of the Mentha spicata L. aqueous extract on Raphanus sativus L. seeds. A completely randomized design was used in a 5x4 factorial scheme with four replications and four extraction methods (infusion, grinding in a blender, drying at 40 °C and 70 °C) and five concentrations (0; 25; 50; 75 and 100%). The variables investigated were: phenolic compounds quantification, germination, germination speed index (GSI), mean germination time (MGT), radish shoot and root length. The extract presenting the highest amount of phenolic compounds was prepared via infusion (724.36 µg/mL), followed by drying at 40 °C (605.07 µg/mL), blending (594.12 µg/mL) and drying at 70 °C (529.36 µg/mL). The Mentha spicata L. aqueous extracts interfered in the radish seed physiological quality, by inhibiting germination, GSI and MGT increase, mainly when in higher concentrations. There was a directly proportional relation between the quantity of phenolic compounds extracted through different extraction methods and the interference in the physiological quality of the radish seeds.